Induced sputum versus bronchoalveolar lavage in lower respiratory tract infection: an exploratory paired diagnostic study - Jiaxi Deng; Haimao Qin; Jie Yang; Yuanyuan Li; Dengfeng Zhou; Bo Zhang; Yushu Ruan (Frontiers in Medicine, 2026)
Introduction Bronchoalveolar lavage fluid (BALF) is widely used for etiologic assessment of lower respiratory tract infection (LRTI), but its invasiveness limits routine use. This study evaluated induced sputum (IS) as a less-invasive specimen for targeted next-generation sequencing (tNGS). Methods In this prospective exploratory study, paired IS and BALF samples from 30 adults with suspected LRTI underwent tNGS. The primary etiology was determined by composite clinical adjudication. Detected microorganisms were classified as definitive pathogens, conditional pathogens, or colonizers/commensals. Results Clinical-match positivity was 70.0% (21/30) for IS and 86.7% (26/30) for BALF, while combining both specimens increased coverage to 93.3% (28/30). Definitive pathogen detection was broadly similar between specimens, whereas colonizers/commensals were more frequently detected in IS (45.6% vs 28.2%). After excluding six Mycoplasma / Mycobacterium cases, clinical-match positivity was 75.0% for IS and 83.3% for BALF (McNemar exact p = 0.688). Discussion Differences between IS and BALF tNGS were mainly attributable to upper-airway background signals. IS may serve as a less-invasive initial option in selected non-complex LRTIs, though further prospective validation in larger cohorts is needed.